Analysis of the Operational Management System for Clean Water Distribution in Permanent Residences after Disasters in Huntap Talise, Palu City - andi asnudin; Nofriyanto; Vera Wim Andiesse; Iffah Fadliah (Inersia: Jurnal Teknik Sipil, 2026)
Sustainable clean water provision in post-disaster permanent housing (huntap) is a fundamental prerequisite for public health recovery and socio-economic restoration. However, comprehensive evaluations of operational management systems for water distribution from a socio-technical perspective remain scarce in disaster literature. Objective: This study analyzes the operational management system of clean water distribution in Huntap Talise, Palu City, following the 2018 multi-hazard disaster, examining infrastructure performance, user satisfaction, and institutional dynamics.  The research employed an explanatory sequential mixed-method design. Quantitative data were collected through surveys of 88 randomly selected households (Slovin formula, α=10%) and analyzed using the Relative Rank Index (RRI) and Spearman's Rho correlation test. Qualitative data were gathered through field observations, in-depth interviews, and focus group discussions, and were then analyzed thematically.  The study revealed dissonance between technical capacity and operational reality. The inflow discharge (22.22 L/sec) theoretically meets the total demand (520,500 L/day). However, RRI identified three critical deficiencies: 24-hour flow continuity (RRI=0.3045), speed of disturbance repair (RRI=0.3227), and disruption frequency (RRI=0.3295). Correlation analysis showed continuity strongly associated with reduced disruptions (r=0.581; p<0.001). Qualitatively, institutional pathologies emerged: ambiguous management status, lack of preventive maintenance, and a design that depends on limited household tank capacity. Conversely, voluntary contribution compliance reached 97%, indicating robust social capital.  This study confirms that post-disaster water system effectiveness is determined not solely by technical sufficiency, but by governance quality and institutional responsiveness. A socio-technical approach integrating institutional strengthening, operational professionalization, and the utilization of social capital is essential for achieving water system resilience in post-disaster permanent housing.  Keywords: Clean Water Distribution, Post-Disaster Permanent Housing, Operational Management, Community Satisfaction, Infrastructure Resilience, Socio-Technical Analysis